2008
DOI: 10.1063/1.2913048
|View full text |Cite
|
Sign up to set email alerts
|

High-k gate stack on germanium substrate with fluorine incorporation

Abstract: In this letter, a postgate CF4-plasma treatment is proposed and demonstrated on germanium (Ge) metal-oxide-semiconductor capacitors and the effects of fluorine (F) incorporation have been studied on both high-k∕Ge gate stacks without any surface passivation and with Si surface passivation. Our results show that F is effectively introduced into the gate stack by CF4 treatment and segregates near high-k∕Ge interface. Electrical characteristics such as frequency dispersion, interface state density (Dit), and gate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 20 publications
0
34
0
2
Order By: Relevance
“…These properties cause high defect densities at the interface between high-k and Ge and a large hysteresis in the capacitance-voltage (C-V) characteristic [8,9]. To overcome these problems, some groups have demonstrated the formation of stable GeO 2 [10,11] and the surface passivation of Ge such as GeN (GeON) passivation [12,13], Si passivation [14], and F passivation [15]. These approaches achieved the improvements of electrical properties such as reduced C-V characteristic hysteresis and reduced leakage current.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These properties cause high defect densities at the interface between high-k and Ge and a large hysteresis in the capacitance-voltage (C-V) characteristic [8,9]. To overcome these problems, some groups have demonstrated the formation of stable GeO 2 [10,11] and the surface passivation of Ge such as GeN (GeON) passivation [12,13], Si passivation [14], and F passivation [15]. These approaches achieved the improvements of electrical properties such as reduced C-V characteristic hysteresis and reduced leakage current.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…NH 3 treatment [8], atomic N surface nitridation [9], SiH 4 treatment [10], wet-NO pretreatment [11], AlN x passivation [12][13][14] and TaO x N y interlayer [7]. Also, it was reported that fluorine was a good passivant for HfO 2 / SiO 2 interface due to formation of strong Hf-F and Si-F bonds [15,16], while Xie et al [17] used F to anneal the HfO 2 in Ge MOS transistors for improved electrical properties.…”
Section: Introductionmentioning
confidence: 98%
“…[9][10][11] Recently, fluorine ͑F͒ incorporation into the high gate dielectric has been shown to improve device performance and reliability on Si substrate [12][13][14] and Ge substrate. 15 Seo et al 13 incorporated F into high gate dielectric by F 2 annealing in the presence of UV radiation, passivating high bulk and high / Si interface defects. Mitani et al 14 introduced F into gate dielectrics by F implantation and followed by annealing.…”
mentioning
confidence: 98%
“…12 The similar mechanism has been reported on Ge substrate that Ge-F and Hf-F bonds formation at high / Ge interface and in HfO 2 gate dielectric results in reduction in interface and bulk traps, respectively. 15 In this letter, we explore the possibility of its inclusion as the gate dielectric in InGaAs-based devices. We demonstrate the impact of postgate CF 4 plasma treatment on In 0.53 Ga 0.47 As n-MOSFET.…”
mentioning
confidence: 99%